HelloTalk Application as an Alternative for Building Students’ Reading Ability on Narative Texts - Zulaikah, Zulaikah; Muklas, Muhammad; Khamahira, Yasina (JOLLT Journal of Languages and Language Teaching, 2024)
English was regarded as a foreign language in Indonesia and holds significant importance in various domains, including education, economy, international relations, and technology. Consequently, the Indonesian government has designated English as the primary foreign language, mandatory for learning in both schools and universities. Thus, English has incorporated into the curriculum from elementary level up to university. This research aimed to determine if there is a significant difference in the reading abilities of students taught using the Hellotalk application compared to those taught through conventional methods.in this school most of students still Â low to read the English text so the Reseacher interesting to give new method for them. The method used Quantitative research, with an experimental method and quasi-experimental design. The target population consisted of seventh-grade students. Purposive sampling was utilized to select a sample of 25 students for the experimental group and 25 students for the control group. Data collection involved the use of a multiple-choice test, which was subsequently analyzed using the independent t-test in SPSS 25. The research findings revealed a significant distinction between the experimental group and the control group. This meant that Hellotalk Application was suitable to use in teaching reading on narrative texts at the seventh grade.